Corticosteroids in the prevention and treatment of infants with bronchopulmonary dysplasia: Part I. systemic corticosteroids. Issue 3 (12th January 2022) - Szabó, Hajnalka; Baraldi, Eugenio; Colin, Andrew A.
Abstract: Bronchopulmonary dysplasia (BPD) is the most significant respiratory complication of prematurity, and its consequences last from birth into adulthood. Unfortunately, the dramatic improvements in the management of premature infants have not led to a decreased incidence of BPD, or to breakthroughs in treatments offered for this long‐lasting chronic respiratory disorder. Over recent decades the pathological picture of BPD has changed from inflammation, interstitial fibrosis and emphysema attributed to volu‐, barotrauma and oxygen toxicity to larger, simplified alveoli and dysmorphic vessels related to arrested alveolarization and vasculogenesis with inflammation maintaining a central role. Corticosteroids (CSs) play a key role in the development of respiratory epithelial cells and lung maturation. These potent anti‐inflammatory agents have long been used for the prevention and treatment of BPD; however, the risk/benefit ratio of their use remains unresolved. CSs administered antenatally have contributed to reduce mortality and respiratory distress syndrome, no such effect on BPD reduction has been observed. Postnatal systemic CSs reduced the rate and severity of BPD, yet their long‐term neurodevelopmental and respiratory consequences markedly limit routine administration. This is the first in a two‐part State‐of‐the‐Art series that reviews the latest relevant clinical trials investigating the short‐term and long‐term effects of CSs in the prevention and treatment of BPD.